Clinical diagnosis and a short-term treatment of bullous pemphigoid in an adult Yemeni female: A case report - Mohamed A Al-Kamel (Our Dermatology Online, 2016)
Bullous pemphigoid (BP) is an acquired, inflammatory, sub-epidermal, immunobullous disease. It usually occurs in the elderly population and reported cases of BP in adults are very rare. This report describes an adult Yemeni female who was clinically diagnosed to have BP, and successfully treated with a steroid containing short term regimen. It concludes the possibility of reaching a clinical diagnosis of BP in disadvantaged areas based on the clinical criteria, and the importance of considering a diagnosis of BP in young adults and even in children who present with itchy tense blisters of forearms, hands and feet. When accessible, further immunofluorescence studies are important to confirm the accuracy of the clinical diagnosis of BP.